Editors play down risk - Mithleshni Gurdayal (Asia Pacific Network, 1999)
The Daily Post's editor, Jale Moala, and news editor, Mesake Koroi disagree with the view that the sale of the nespaper is a threat to media independence. In this interview, they make a rare statement, defending the Daily Post's independence.